Comprehensive Treatment Strategy for Chronic Low Back Pain in a Patient with Bilateral Transfemoral Amputations Integrating Changes in Prosthetic Socket Design. Issue 4 (October 2017) - Mazzone, Brittney; Yoder, Adam; Zalewski, Brian; Wyatt, Marilynn; Sheu, Robert
ABSTRACT: Introduction: Wounded service members with amputations undergo a complex rehabilitation regimen that can often become complicated by skin breakdown, heterotopic ossification (HO), and pain of the residual limb, contralateral limb, or low back. These complications can impact prosthetic socket fit, decreasing one's functional independence, and potentially negatively impact quality of life. The purpose of this report is to present a case involving the treatment of HO along with prosthetic socket modifications, with the intention to address low back pain (LBP), in a patient with bilateral transfemoral amputations. Materials and Methods: The patient experienced traumatic bilateral amputations as a result of an improvised explosive device blast. He was initially fit with ischial containment sockets to provide stability and enhance early mobility. He became a community ambulator but was experiencing LBP and issues with HO. After extensive HO resection, a multidisciplinary discussion took place to determine the best way to diminish LBP by improving spinopelvic alignment while restoring function. It was decided to refit the patient with subischial containment sockets. Subjective questionnaires and three-dimensional gait analysis were used to quantify results. Results: After HO resection and prosthetic socket modifications, the patient's complaints of LBP decreased, along with subjective improvements in the Oswestry Disability Index and Short Musculoskeletal Functional Assessment. During upright standing, anterior pelvic tilt decreased from 27.6° to 18.1°. During walking, excursion of the trunk relative to the pelvis decreased in all planes after changing prosthetic socket design to subischial and completing 6 months of rehabilitation: from 24.0° to 17.6° in the frontal plane, 12.4° to 7.8° in the sagittal plane, and 23.1° to 19.1° in the transverse plane. Conclusions: A multidisciplinary team approach to the care of patients with bilateral transfemoral amputations can help to improve functional outcomes. For this patient with nonradicular, mechanical LBP, a subischial prosthetic socket design that minimized intrusion on the pelvis had a significant influence on static and dynamic sagittal spinopelvic alignment and overall outcomes. In the end, contributions by orthopedic and plastic surgeons, pain management strategies by a physical medicine and rehabilitation physician, rehabilitation by a physical therapist, and prosthetic modifications all played a role in reduction of this patient's LBP. Among the numerous interventions provided to this patient, including surgical revisions, prosthetic socket design, prosthetic alignment, and physical therapy, it is hypothesized that the change in prosthetic socket design from ischial containment to subischial had a significant, long-lasting impact on LBP and function.